EFFECTS OF ADDING THE DRY NEEDLING TO GUIDELINE-ENDORSED PHYSICAL THERAPY IN PATIENTS WITH CHRONIC NECK PAIN: A RANDOMIZED CONTROLLED TRIAL - Stieven, F. F.; Ferreira, G. E.; Wiebsch, M.; Rosa, L. H.; Silva, M. F. (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2019)
DESIGN: Randomized controlled trial. BACKGROUND: Recents clinical guidelines certify both exercise and manual therapy as effective treatment for patients with chronic neck pain. Aiming for a better clinical effect, the dry needling (DN) is used in these patients. OBJECTIVES: To determine the effects of DN in patients with chronic neck pain pain when added to a physical therapy program consisting of exercise and manual therapy. METHODS: 116 patients with chronic nonspecific neck pain were randomly allocated to receive one month of physical therapy, consisting of exercise and manual therapy, or the same treatment with the addition of DN applied to the neck muscles. The primary outcomes were pain intensity (24-hour neck pain and 1-week neck pain) and disability (1 month after randomization) and the secondary outcomes were pain intensity, disability (3 and 6 months after randomization), global perceived effect, quality of sleep and catastrophysing. RESULTS: Differences were observed between groups in the primary end points of pain intensity (24-hour neck pain: mean difference, -1.30 points, 95% CI -0.84, -176; 1-week neck pain: mean difference -1.53 points, 95% CI -2.26,-0.80) but not for disability (mean difference, -0.43 points, 95% CI: -0.96, 1.82) after 1 month follow-up. In addition, no differences were observed between the groups for the other outcomes. CONCLUSION: Patients who received a physical therapy program consisting of exercises and manual therapy obtained additional benefits with the use of DN to reduce neck pain, but there were additional benefits for reducing disability, perception of treatment effect, sleep quality and catastrophization.